Graeco-Latin terminology of clinical dentistry - Rollerová, Anna; Vasiľová, Linda (Comenius University in Bratislava, 2018)
Dental clinical terminology provides students with knowledge of other medical disciplines such as phoniatrics, paediatrics, pathology, ophthalmology, neurology, psychiatry, and otorhinolaryngology. For this reason, the vocabulary of the textbook has been excerpted from various clinical fields, while still focusing on vocabulary obtained from publications in dentistry and maxillofacial surgery.